2012
DOI: 10.1007/s00441-012-1417-5
|View full text |Cite
|
Sign up to set email alerts
|

Localization of breast cancer resistance protein (Bcrp) in endocrine organs and inhibition of its transport activity by steroid hormones

Abstract: Breast cancer resistance protein (BCRP) is known for its protective function against the toxic effects of exogenous compounds. In addition to this, a role in the transport of endogenous compounds has been described. Since BCRP in the plasma membrane was shown to be regulated by sex steroids, we investigated the presence and possible role of BCRP in steroid hormone-producing organs. Therefore, the presence and localization of Bcrp was investigated in endocrine organs of wild-type mice. Furthermore, the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 42 publications
2
37
0
Order By: Relevance
“…In the testes, previous studies have shown that Bcrp is expressed mostly in endothelial cells of microvessels in the interstitium and in peritubular myoid cells in the tunica propria of both humans and mice 3,20,21 (Figure 2). Thus, Bcrp is not localized to the BTB in the testes.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…In the testes, previous studies have shown that Bcrp is expressed mostly in endothelial cells of microvessels in the interstitium and in peritubular myoid cells in the tunica propria of both humans and mice 3,20,21 (Figure 2). Thus, Bcrp is not localized to the BTB in the testes.…”
Section: Introductionmentioning
confidence: 93%
“…Additionally, the activity, expression and cellular distribution of Bcrp are regulated by steroids. 21,41,42 Collectively, these findings indicate an intimate physiological relationship between Bcrp and the androgen and/or oestrogen microenvironment in the testes, but there are no reports in the literature to assess the role of Bcrp in regulating the level of steroids in the seminiferous epithelium, interstitial fluid and/or the rete testis compartment. However, Bcrp 2/2 male mice are fertile, 47 even though these mice display a malfunction in the disposition of phytoestrogens (e.g., genistein, daidzein, coumestrol), 48 suggesting that while it is important to testicular function, its loss in function via deletion in male mice can be superseded by other ABC drug transporters, such as P-glycoprotein and Mrp1.…”
Section: Substratesmentioning
confidence: 98%
See 2 more Smart Citations
“…PMS generation could be secondary to enhanced progesterone synthesis because progesterone has been found to stimulate SULT1E1 expression in human endometrial adenocarcinoma cells [39]. Interestingly, progesterone is able to inhibit ABCG2 [40] and hence may affect the ability of the placenta to export ABCG2 substrates toward the maternal circulation.…”
Section: Concentration (Mm)mentioning
confidence: 99%